2013
DOI: 10.1136/bcr-2013-008741
|View full text |Cite
|
Sign up to set email alerts
|

Keratocystic odontogenic tumour (KCOT) misdiagnosed as a dentigerous cyst

Abstract: SUMMARYKeratocystic odontogenic tumours are known for their peculiar behaviour, varied origin, debated development, unique tendency to recur and disputed treatment modalities. Thus, it has been the subject of much research over the last 40 years. It was formerly known as odontogenic keratocyst (OKC). OKC received its new title as keratocystic odontogenic tumour (KCOT) by the WHO (2005) in order to suggest its aggressive and recurrent nature. KCOT is a benign intraosseous neoplasm of the jaw. Involvement of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 8 publications
(4 reference statements)
1
12
0
3
Order By: Relevance
“…Till date, only a handful of cases has been reported of KCOT crossing maxillary midline [6]. When KCOT occurs in maxilla, diagnostic difficulties arise owing to lack of characteristic clinical and radiographic features [2]. The maxillary KCOTs are usually smaller in size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Till date, only a handful of cases has been reported of KCOT crossing maxillary midline [6]. When KCOT occurs in maxilla, diagnostic difficulties arise owing to lack of characteristic clinical and radiographic features [2]. The maxillary KCOTs are usually smaller in size.…”
Section: Discussionmentioning
confidence: 99%
“…It was reclassified by WHO (2005) as a benign tumor, and the use of term KCOT was recommended as it reflects on its neoplastic nature [1]. Often due to atypical clinical and radiographic presentations, KCOTs have been misdiagnosed as odontogenic cysts (viz., dentigerous cyst, radicular cyst, and lateral periodontal cyst) and have been undertreated [2][3][4]. Since KCOT has an aggressive biological behavior, it is essential to distinguish it from odontogenic cysts [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the best way to confirm its diagnosis is by recognizing its characteristic histopathologic features 2. The histopathologic features of KCOT are confirmatory with distinctly different epithelial lining.…”
Section: Discussionmentioning
confidence: 99%
“…However, in 1967, Toller suggested that the OKC should rather be regarded as a benign neoplasm and not as a typical cyst 2. Ever since Mikulicz presented the first case of OKC, in 1876, as a “dermoid cyst,” this interesting lesion has been the subject of debate owing to its varied origin, debated development, peculiar behavior, unique tendency to recur, and disputed treatment modalities 3…”
Section: Introductionmentioning
confidence: 99%
“…In fact, dentigerous cyst and KCOT can share clinical and radiological features; furthermore, KCOT may have the gross appearance of a dentigerous cyst in some cases, so that a correct diagnosis can only be made by histopathological analysis (5).…”
Section: Introductionmentioning
confidence: 99%